PENGEMBANGAN MEDIA MAGIC BOX BERBASIS DEMONSTRASI PADA PEMBELAJARAN MATEMATIKA KPK DAN FPB DI KELAS IV SD - Fany Rahmasari; Nila Lestari (Jurnal Inovasi Penelitian, 2023)
This study aims to development demonstration-based MangicBox media in KPK and FPB mathematics learning and measure the feasibility of these products so that they can be used as learning media in class 4 SD. This research uses a research and development approach (R&D), the development model used in this research is development capital ADDIE (analysis, design, development, implementation, evaluation). product trials carried out in SDN No. 106450 Cinta air in grade 4 by the number of students 18 students people. the result of the research is the development-based Magic Box media on KPK dan FPB mathematics learning in class 4 SDN No. 106450 Cinta Air. there are three result from the study, the first is the assessment of material aspects by 89% categorized as “vary decent” media feasibility aspect assessment is 93,3% has a valid category of “very decent” and the assessment of learning experts by 90% in the “Very feasible” category. Based on these results, it can box learning media is feasible to be applied in learning mathematics in grade IV Elementary School.